Molecular dynamics studies on the sintering and mechanical behaviors of graphene nanoplatelet reinforced aluminum matrix composites. (4th June 2019) - He, Huiping; Rong, Yan; Zhang, Lan
Abstract: The sintering process of graphene nanoplatelet (GNP) reinforced aluminum matrix composite powder was simulated by molecular dynamics method. The effects of Al nanoparticle size and sintering temperature on sintering behavior were studied. Uniaxial tensile simulation was applied to study the mechanical properties of sintered composites. The results show that the nanoparticle size and sintering temperature have significant effects on the sintering behavior of the composites. Smaller size nanoparticle system has lower melting point, which requires lower sintering temperature. Larger size particle system requires longer sintering time and higher sintering temperature. At lower temperatures, the main coalescence mechanisms of nanoparticle systems are surface diffusion and grain boundary diffusion. When the temperature is close to the melting point, volume diffusion and surface diffusion dominate. Tensile simulation results of sintered composites show that the addition of GNP can greatly improve the mechanical properties of the composites. Dislocation reinforcement and stress transfer are the main reinforcement mechanisms.